REV-OPOLY: An Immersive Augmented Reality Board Game Experience - Nordin, Noradila; Mohd. Nordin, Nur Rasyidah; Omar, Wafa (Multidisciplinary Applied Research and Innovation, 2021)
Due to the current strict isolation measures during the pandemic, learners from all parts of the world are confined to their homes under the new norm. As a result, massive educational disruptions have occurred, causing education to be conducted virtually. In comparison to traditional learning, virtual learning requires proper redesigning of a course to overcome challenges particularly in content-related activities, engagement, and communication as learners may feel isolated during lessons. Due to these setbacks, the learners have demonstrated ineffective learning as well as a lack of interest and motivation to participate in virtual classes. To address these issues, it is hoped that the use of gamification will introduce game elements into the educational context while also instilling a sense of fun in learning. Thus, this research proposed REV-OPOLY, an interactive monopoly-inspired board game with augmented reality (AR). By infusing the board game with AR, it has opened up the possibilities of strengthening the process and experience in learning. REV-OPOLY enables interactive lessons by combining virtual and real environments while promoting valuable social skills for players through interaction and competition. REV-OPOLY concentrates on the emerging technology revolution, which is a part of the Computer Application in Management curriculum offered at Universiti Utara Malaysia. It consists of a board, player pieces, and cards that act as AR markers. Each of these can be scanned to reveal 3D characters or information in the form of 3D texts, images, animations, and videos. REV-OPOLY’s AR only requires a connection to the Internet, and it supports any type of web browser. REV-OPOLY opens up a new learning experience for learners as an alternative to the typical learning method. The findings showed that the participants enjoyed and were satisfied with learning through REV-OPOLY. REV-OPOLY helps to assist and enhance learners’ comprehension levels while enjoying the learning process.